Coexistence of Tourism in Urban Planning: Active Living, Social Sustainability, and Inclusivity - Liasidou, Sotiroula; Stylianou, Christiana (My University, 2024)
In any city, various social groups coexist and need to have a harmonious symbiosis and optimise how people experience the city. The notion of urban planning incorporates positive city development that is active, socially sustainable, and inclusive. This study aims to identify whether the development of the Mediterranean city of Limassol, Cyprus extends to cover the needs of people with disabilities (PwD), residents, and tourists, emphasising physical impairments regarding the facilities and services provided. Limassol, Cyprus is an interesting case because recent developments aim to establish the city as a friendly living space with varied activities and services. Additionally, the city attracts tourists, and such development can be a competitive advantage as a tourism destination. Semi-structured interviews with PwD have been conducted to analyse their views, aiming to identify the extent to which existing infrastructure and services align with an inclusive model within the framework of sustainability, encompassing the notion of an active city. According to the findings, local government via municipal and tourism authorities should consider inclusivity in all aspects when re-developing urban settings by ensuring accessibility for PwD and offering more services that adhere to the requirements of an active, socially sustainable, and inclusive city.
Keywords: active city; Cyprus; inclusion; people with disabilities; qualitative research; social sustainability; urban planning